Utilization of, satisfaction toward, and challenges for Internet-based healthcare services provided by primary health institutions: Evidence from China - Wang, Shuo; Wang, Xin; Zhou, Yuyin; Xu, Junfang (Frontiers in Public Health, 2023)
Background: The rapid development of “internet plus healthcare” in China has provided new ways for the innovative development of primary health care. In addition, a series of favorable policies have been issued to promote the internet-based healthcare services in primary health institutions. The aim of this study was to describe the utilization of, satisfaction towards, and challenges faced by internet-based healthcare services provided by primary health institutions in China. Methods: A self-designed structured questionnaire was employed to collect related data. The questionnaire included social-demographic characteristics, health related information, utilization of, satisfaction towards and challenges faced by internet-based healthcare services provided by primary health institutions. Wilcoxon rank sum test was carried out to examine the differences in the satisfaction with internet-based healthcare services between participants who ever received these services and those who did not. Multiple logistic regression model was also used to examine the factors influencing the utilization of internet-based healthcare services provided by primary health institutions. Results: A total of 10600 residents were included in the final analysis, of whom 5754 (54.3%) were women. 51.3% (5434) of them ever used internet-based healthcare services provided by primary health institutions. Among those who used, the most widely used services were procedures related consultation services (63.7%). The satisfaction among those who ever used it was significantly higher than that among those who did not (84.7% vs 45.4%; p-value<0.001). One of the biggest challenges (69.3%) expressed by the residents was that it was difficult for the elderly to use internet-based services. Younger people, people with lower education levels, and people with chronic diseases were significantly more likely to use internet-based healthcare services provided by primary health institutions (P<0.05). Conclusion: More than half of people used internet-based healthcare services provided by primary health institutions among 10600 residents surveyed in China in 2020, and most of them were satisfied although subgroups significant differences existed. The most common use was procedure related and several challenges of using internet-based healthcare services exist. Therefore, it is important to further improve internet-based primary healthcare services based on the population’ perception for achieving healthy China 2030.